Pendampingan Belajar Peserta Didik dalam Menyelesaikan Soal Tipe HOTS pada Materi Matriks - Nur, Fitriani; Amin, Badaruddin; Fatmah, Nurul; D, Azmin; Nursalam (KHIDMAH: Jurnal Pengabdian Masyarakat, 2024)
Higher Order Thinking Skills (HOTS) are high-level thinking skills that involve analysis, evaluation and creation. In line with the implementation of a curriculum that emphasizes HOTS development, there are still obstacles in students' ability to face HOTS questions, especially in matrix material. Some students experience difficulty in applying matrix concepts analytically and critically in solving problems that require high-level thinking. This service is assisting class XI students in Package 9 MAN 2 Makassar City, which aims to improve students' abilities in solving HOTS questions on matrix material. The service is carried out with an interactive approach and is based on practical exercises related to HOTS questions. Evaluation of the level of success of service is carried out through learning outcomes tests which include HOTS questions and student response questionnaires. Based on the analysis of learning outcomes tests, the average student score was 58.68 in the medium category. Meanwhile, the results of the analysis of student responses obtained a response percentage of 91,11 in the very positive category. The results of this evaluation show that learning assistance in solving HOTS questions is really needed by students. Thus, service activities are recommended to be carried out on an ongoing basis in an effort to improve students' HOTS abilities.